Analysis of in-vivo articular cartilage contact surface of the knee during a step-up motion. (November 2017) - Yin, Peng; Li, Jing-Sheng; Kernkamp, Willem A.; Tsai, Tsung-Yuan; Baek, Seung-Hoon; Hosseini, Ali; Lin, Lin; Tang, Peifu; Li, Guoan
Abstract: Background: Numerous studies have reported on the tibiofemoral articular cartilage contact kinematics, however, no data has been reported on the articular cartilage geometry at the contact area. This study investigated the in-vivo tibiofemoral articular cartilage contact biomechanics during a dynamic step-up motion. Methods: Ten healthy subjects were imaged using a validated magnetic resonance and dual fluoroscopic imaging technique during a step-up motion. Three-dimensional bone and cartilage models were constructed from the magnetic resonance images. The cartilage contact along the motion path was analyzed, including cartilage contact location and the cartilage surface geometry at the contact area. Findings: The cartilage contact excursions were similar in anteroposterior and mediolateral directions in the medial and lateral compartments of the tibia plateau ( P  > 0.05). Both medial and lateral compartments were under convex (femur) to convex (tibia) contact in the sagittal plane, and under convex (femur) to concave (tibia) contact in the coronal plane. The medial tibial articular contact radius was larger than the lateral side in the sagittal plane along the motion path ( P  < 0.001). Interpretations: These data revealed that both the medial and lateral compartments of the knee experienced convex (femur) to convex (tibia) contact in sagittal plane (or anteroposterior direction) during the dynamic step-up motion. These data could provide new insight into the in-vivo cartilage contact biomechanics research, and may provide guidelines for development of anatomical total knee arthroplasties that are aimed to reproduce normal knee joint kinematics. Highlights: Both medial and lateral sides of the knee were under convex to convex contact in sagittal plane. Tibiofemoral contact locations moved toward the intercondylar areas during the step-up motion. Medial and lateral cartilage contact geometries were similar in pattern, different in dimension.